Harmattan: A Philosophical Fiction - Jackson, Michael (Insurrections: Critical Studies in Religion, Politics, and Culture, 2015)
A slim but thoughtful rendering of an exotic locale that recalls The Quiet American. Stefania Pandolfo, UC Berkeley:A philosophical and literary exploration of the limits of life and the norm, Michael Jackson's fascinating new book travels the geographical, psychological and political borderland of social life and 'the more' that lies beyond. It spans the boundary of historical event and mythical reality, war and peace, ethnography, fiction, and autobiography, to ponder the potential that, as he puts it, lies beyond the pale of our established life worlds. The search for the sources of life encounters and passes through death. In that passage the self dissolves and multiplies, and its characters exchange their places and are projected onto an imaginal space where West African, European and Oceanian worlds echo and reflect upon each other, and a society reveals to itself the enigma of its vital and destructive core. For, as we are told, at one time or the other, Europe has also been one of the dark places of the earth. Harmattan's characters are unforgettable: Ezechiel, surviving the civil war in Sierra Leone and migrating to the North and the halls of the British Library, Tom, an anthropologist's alter, making the reverse journey to the uncanny tranquility of Ezechiel's post civil war ravaged village, Cosmega, the woman who was not undone by the wreckage, a Kuranko shaman finding his power and overcoming his fear, and then dying, and an ethnographer encountering himself, or herself, as another, on the borderland where being is both lost and found. In the literary tradition of Calvino and Pessoa, Conrad and Tutuola, but also Vict